A comparative study on witness protection program in criminal cases in Malaysia and other jurisdictions / Nurul Nadia Hartini Rosehan and Nurulhajar Adini Adzhan Izani - Rosehan, Nurul Nadia Hartini; Adzhan Izani, Nurulhajar Adini (2008)
Introduction: This study is a comparative study of a witness protection program in Malaysia and other jurisdictions. Purpose: The purpose of choosing this topic of study is to observe and gauge the Malaysian attitude to these categories of witnesses who would normally refuse to testify because of fear of intimidation. There is no specific law that deals with witness protection program in Malaysia. In view of this we have decided to embark on this comparative study. Finding: The result indicated that there was a significant difference on the program in the respective countries. We have compared the program with other jurisdictions such as United States, European countries and also outside the European countries. Result: It was an interesting comparison wherein we can actually differentiate the flow of the witness protection program in otlier countries. Unfortunately, there are no specific provisions on witness protection program in Malaysia. We only look into the relevancy of the Chapter IX of the Evidence Act 1950 (Act 56) regarding witnesses and the Criminal Procedure Code (ACT 593).